2023
DOI: 10.1111/den.14606
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound‐guided gallbladder drainage as a first approach for jaundice palliation in unresectable malignant distal biliary obstruction: Prospective study

Abstract: ObjectivesEndoscopic retrograde cholangiopancreatography (ERCP) represents the gold standard for jaundice palliation in patients with distal malignant biliary obstruction (DMBO). Biliary drainage using electrocautery lumen apposing metal stent (EC‐LAMS) is currently a well‐established procedure when ERCP fails. In a palliative setting the endoscopic ultrasound‐guided gallbladder drainage (EUS‐GBD) could represent an easy and valid option. We performed a prospective study with a new EC‐LAMS with the primary aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…The development of the LAMS in particular has greatly facilitated performing EUS-CD and EUS-GE, thus enabling one-step stent placement, which can reduce procedure time and decrease the rate of adverse events. While the majority of studies on LAMS have utilized one particular device (Hot AXIOS, Boston Scientific, Marlborough, MA, USA), it should be noted that other LAMS devices have also been examined (Hot Spaxus, Taewoong Medical, Kimpo, Republic of Korea) for these indications [ 69 , 70 ]. While data reporting regarding these procedures and their adverse events remains an ongoing process, one must remember that all the reported studies involve expert centers with highly experienced endoscopists and for the time being, we recommend referral to tertiary centers with a high comfort level for these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the LAMS in particular has greatly facilitated performing EUS-CD and EUS-GE, thus enabling one-step stent placement, which can reduce procedure time and decrease the rate of adverse events. While the majority of studies on LAMS have utilized one particular device (Hot AXIOS, Boston Scientific, Marlborough, MA, USA), it should be noted that other LAMS devices have also been examined (Hot Spaxus, Taewoong Medical, Kimpo, Republic of Korea) for these indications [ 69 , 70 ]. While data reporting regarding these procedures and their adverse events remains an ongoing process, one must remember that all the reported studies involve expert centers with highly experienced endoscopists and for the time being, we recommend referral to tertiary centers with a high comfort level for these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported a technical success rate of 100 % and a clinical success rate of 81.3 %, with a mean total bilirubin reduction after two weeks of 66.5 % and an AEs rate of 10.4 % [53]. Moreover, EUS-GBD was considered a valid first-line option for BD for low-survival patients with unresectable DMBO, as shown in 37 patients with 100% technical and clinical success rates and an AEs rate of 10.8% [54]. Possible complications of EUS-GBD include bleeding, cholangitis/cholecystitis, bile leak, sepsis, peritonitis, stent migration and perforation.…”
Section: Eus-guided Gallbladder Drainage (Eus-gbd)mentioning
confidence: 96%
“…EUS-GBD has also been investigated as a primary drainage technique in distal MBO. A prospective study including 37 consecutive patients reported 100% technical and clinical success, with 10.8% adverse events, including three stent disfunctions secondary to food impaction (n = 1) and cystic duct obstruction due to neoplastic progression (n = 2) [81]. Beyond the understandable enthusiasm with such good results, it should be recognized that long-term clinical data are still scarce, and we still do not know how reliable this route of drainage will be over time, especially in patients with a cystic duct that takes off very close to the neoplastic mass [82,83].…”
Section: Eus-gallbladder Drainage As a Rescue Strategy In Malignant B...mentioning
confidence: 99%